Imobilização da enzima ß-galactosidase em suporte de quitosana - Damin, Brenda Isadora Soares (2022)
β-galactosidase enzyme has a great potential for application in the food industry due to its ability to carry out the hydrolysis of lactose, a disaccharide present in milk, whey, and dairy products. The enzyme can be used in the free form, in batch processes, or immobilized, allowing continuous operation and providing greater enzymatic stability. The choice of the method and the support for enzyme immobilization is fundamental since the performance of the biocatalyst is strongly influenced by the properties of the material used and by the mechanisms of interaction between support and enzyme. Physical adsorption is a simple and most commonly used immobilization method, and it can be reconciled with cross-linking. Allied to this, biopolymers are promising materials for enzymatic immobilization, mainly due to the non-toxicity and the availability of numerous reactive sites. Chitosan, due to its amine groups presents a strong interaction with the enzyme and can be used to form a composite with silica, to combine its properties and increase the stability of the immobilized enzyme. In this sense, this work aimed to evaluate the enzyme supports developed from chitosan for the immobilization of the β-galactosidase enzyme (Kluyveromyces lactis). For this, two approaches of the development of chitosan-based supports were evaluated. The first consists of a support developed by dropping chitosan solution into a coagulation solution containing 1 mol L-1 sodium hydroxide and 26% ethanol (v/v). The second is the synthesis of adsorbent composites based on chitosan and silica obtained by the sol-gel technique (xerogels). The xerogels were developed from different concentrations of glutaraldehyde to verify the influence of the crosslinking agent addition. Regarding the chitosan supports obtained by coagulation, the immobilization pH and the enzyme concentration were optimized for 6.0 and 5.0 mL L-1. Under these conditions, the immobilization efficiency and the degree of enzyme inactivation were 27% and 69%, respectively. After six cycles of reuse, the biocatalyst maintained 56% of immobilization efficiency. The support produced by the sol-gel technique (xerogel) showed immobilization efficiency between 15.83% and 17.38%. The crosslinking of chitosan with glutaraldehyde increased the degree of enzyme inactivation. However, crosslinking increased the immobilization efficiency up to a concentration of 2:1 (glutaraldehyde: chitosan monomer units, mol: mol). Therefore, the chitosan support obtained more promising results for the immobilization of the β-galactosidase than chitosan/silica xerogels. The results obtained attribute to the chitosan support developed an alternative to enable the use of the enzyme in the food industry.